2019
DOI: 10.1002/mame.201900148
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Polymer Adhesive for Aluminized Coatings: From Improved Barrier Properties to Commercial Formulation

Abstract: The development and formulation of core–shell latex‐based adhesives to improve the adhesion of aluminium to poly(ethylene terephthalate) (PET) films and enhance the permeability of the final laminate to oxygen and water is described. All particles have a soft acrylic component (the shell in core–shell particles) to improve adhesion, and occasionally a hydrophobic core to enhance the permeability. The performance of the different latexes is compared to that of a commercially available reference material. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The composite polymeric latexes with two or more distinct phases may have various compositions that lead to different properties, such as high and low glass transition temperatures, hydrophobicity, reactivity, etc., which affect the properties of the final polymer. Several studies were reported on the preparation of composite latexes for various purposes [22][23][24][25][26][27][28][29][30][31][32][33][34]. Among these studies Limousin et al [22] synthesized hybrid latex particles containing a hard, high T g seed (styrene(S)/acrylamide (AM), T g = 101 degrees C) and a low T g (methyl methacrylate (MMA)/butyl acrylate (BA)/styrene(S), T g = 13 degrees C) second phase polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composite polymeric latexes with two or more distinct phases may have various compositions that lead to different properties, such as high and low glass transition temperatures, hydrophobicity, reactivity, etc., which affect the properties of the final polymer. Several studies were reported on the preparation of composite latexes for various purposes [22][23][24][25][26][27][28][29][30][31][32][33][34]. Among these studies Limousin et al [22] synthesized hybrid latex particles containing a hard, high T g seed (styrene(S)/acrylamide (AM), T g = 101 degrees C) and a low T g (methyl methacrylate (MMA)/butyl acrylate (BA)/styrene(S), T g = 13 degrees C) second phase polymer.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the morphology of hybrid latex particles influenced the mechanical strength of polymer films. Lara et al [26] also prepared core-shell latexbased adhesives to improve the adhesion of aluminum to poly (ethylene terephthalate) (PET) films and enhance the permeability of the final laminate to oxygen and water by using a soft acrylic component (the shell in core-shell particles) to improve adhesion, and occasionally a hydrophobic core to enhance the permeability. Zhang et al [29] prepared PVAc-based inverted core/shell (ICS) structured latex adhesive with improved water-and heat-resistance by a copolymerizing-grafting sequential reaction approach for wood bonding.…”
Section: Introductionmentioning
confidence: 99%